A quantitative examination of competition, coopetition and cooperation in supply chains - M. Sepehri; K. Fayazbakhsh (South African Journal of Business Management, 2011)
Traditionally, the members of a supply chain compete to reduce their individual costs. However, as collaborative supply chain approach is urged within industries to reduce the overall costs, either full cooperation or partial coopetition is considered by the members. In cooperative approach, members benefit from lower overall costs and lower cost variations. But individually, some seem better off in a competitive approach in a single period considering their local costs. Coopetition, or partial cooperation, may be suggested as a compromise to lower overall supply chain costs, while members choose alliances towards lower average costs and cost variations.A multi-stage, multi-member, multi-product and single period supply chain model is considered with deterministic demand, capacity and cost. Product prices are assumed to be constant. The objective is to minimize total production and distribution costs of the overall chain. Four distinct cases are considered, modeled, simulated and compared. These cases are complete competition, integrated cooperation, two-stage supply chain partition, and partial coopetition. Quantitative conclusions from the cost performance ratios are drawn using the simulation results.
Keywords: 650